Analisis Lingkungan Kerja Dalam Meningkatkan Kinerja Pegawai Badan Narkotika Nasional Kabupaten Karawang - Akmal, Muhammad; Rismayadi, Budi; Pertiwi, Wike (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Employee performance is influenced by their workplace. Aspects of the workplace will improve along with employee performance. With regard to elements of the work environment, optimal work achievement will be facilitated by an appropriate work environment. This observation aims to find out how the work environment can be analyzed to improve the performance of BNNK Karawang employees. This article was written using a qualitative descriptive research methodology. Observation, interviews, documentation, data reduction analysis techniques, data presentation, and drawing conclusions are the data collection methods used. The results of the research show: Physical and non-physical work environments have a conducive role in improving the performance of BNNK Karawang employees. There are obstacles faced by BNNK Karawang in the form of physical work environments and work equipment that are still not supportive because they have not been replaced and some tools are not modern. The efforts made by BNNK Karawang, that is, in terms of facilities, it can complete the equipment facilities and it is also expected to upgrade equipment facilities that are still simple to equipment that already has the latest technology, there is an increase in performance every year for BNNK Karawang employees.